Current treatment of cervical carcinoma - Bedoya Hevia, Mariano (2015)
Total hysterectomy with resection of 1/3 of the vagina and parametrium, with or without bilateral oophorectomy, is recommended for State "0" of Epidermoid Carcinoma of the Cervix. In State I the therapeutic measure depends on the sensitization response (SR) which would indicate whether surgery or radiation should be use. lf surgery is indicated, radical total hysterectomy with node dissection should be performed. Radiation is the method of election for State II, except in thouse cases in which there is a poor "radiation response" (RR). Radical hysterectomy with node dissection should be the treatment in the surgical cases of this group. We have no doubt that the cytological evaluation by means of the "SR" and "RR" responses is a great help in the selection of the treatment. In State III and IV, radiation is the method of election. If recurrence occurs after radiation therapy pelvic exenteration should be contemplated. In carcinoma of cervical stump the surgery is the choice treatment. In the pregnancy the treatment is in relationship with the viability of the fetus, and grade of the development of tumor. In the carcinoma of fundus which would indicate wheather surgery or radiation.